Unrecorded alcohol consumption in seven European Union countries - Manthey, Jakob; Probst, Charlotte; Kilian, Carolin; Moskalewicz, Jacek; Sierosławski, Janusz; Karlsson, Thomas; Rehm, Jürgen (European addiction research, 2020)
Introduction: Unrecorded alcohol, that is, alcohol not reflected in official statistics of the country where it is consumed, contributes markedly to overall consumption of alcohol. However, empirical data on unrecorded alcohol consumption are scarce, especially in high-income countries. This study measures the contribution of unrecorded alcohol in 7 member states of the European Union. Methods: Two categories of unrecorded consumption were assessed in general population surveys (reducing alcohol related harm Standardized European Alcohol Survey; n = 11,224): home-made alcohol and cross-border shopping. Country-specific logistic regressions were used to link respondent characteristics to odds of acquisition of unrecorded alcohol. Total per capita alcohol consumption was estimated under different assumptions of calculating unrecorded alcohol consumption. Results: Individuals with higher drinking levels were more likely to acquire unrecorded alcohol in all 7 countries. In some countries, male sex and more affluent social class were also positively linked to acquisition of unrecorded alcohol. There was a substantial contribution of unrecorded alcohol to overall consumption in 5 out of 7 member states (Croatia, Finland, Greece, Hungary, Portugal), but not in Poland or Spain. In Greece, up to two-thirds of all alcohol consumed was estimated to be unrecorded. Conclusion: Unrecorded alcohol contributes to overall consumption even in high-income countries, and thus needs to be monitored. In monitoring, as many categories of unrecorded alcohol as possible should be clearly defined (e.g., surrogate alcohol) and included in future surveys.